2013
DOI: 10.1111/socf.12020
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Job Insecurity in Explanations of Racial Health Inequalities

Abstract: The literature documenting substantial health differences for racial minorities in the United States is well developed and has considered a multitude of explanations for such disparities. However, the literature seldom addresses the health effects for racial minorities produced in the workplace. This study bridges these two literatures in order to understand the mediating role of job insecurity in explanations of racial health disparities. Our central argument is that racial differences in job insecurity resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 63 publications
(88 reference statements)
2
40
0
Order By: Relevance
“…Many of these studies have noted significant racial disparity in perceived job insecurity (Elman and O'Rand 2002;Wilson et al 2006;Wilson and Mossakowski 2009) in that black workers have the highest perceived job insecurity and white workers the lowest. One study documents that the perception of job insecurity for black workers is twice as high as it is for white workers (Manski and Straub 2000), another study reports that not only racial disparities in job insecurity exist, but also such difference explains a portion of racial disparities in health PERCEIVED JOB INSECURITY (Fullerton and Anderson 2013). These studies have suggested that a host of factors such as differences in human capital, occupational characteristics, and labor market experience account for the racial disparity in perceived job insecurity.…”
Section: Race and Perceived Job Securitymentioning
confidence: 94%
See 1 more Smart Citation
“…Many of these studies have noted significant racial disparity in perceived job insecurity (Elman and O'Rand 2002;Wilson et al 2006;Wilson and Mossakowski 2009) in that black workers have the highest perceived job insecurity and white workers the lowest. One study documents that the perception of job insecurity for black workers is twice as high as it is for white workers (Manski and Straub 2000), another study reports that not only racial disparities in job insecurity exist, but also such difference explains a portion of racial disparities in health PERCEIVED JOB INSECURITY (Fullerton and Anderson 2013). These studies have suggested that a host of factors such as differences in human capital, occupational characteristics, and labor market experience account for the racial disparity in perceived job insecurity.…”
Section: Race and Perceived Job Securitymentioning
confidence: 94%
“…Such pessimistic perceptions of job security are highly consequential. For example, racial disparity in perceived job insecurity explains racial disparities in health between white and black workers (Fullerton and Anderson 2013).…”
mentioning
confidence: 99%
“…Finally, previous scholarship has documented the impact of job quality on health, and physical health has an effect on overall happiness (Yang ). In particular, scholars have noted that job insecurity and income impact health (Burgard, Brand, and House , ; Coverdill, López, and Petrie ; Cummings and Braboy Jackson ; Fullerton and Anderson ). Furthermore, high work intensity often leads to suboptimal health (Anderson‐Connolly et al.…”
Section: Connecting Job Quality To Subjective Well‐beingmentioning
confidence: 99%
“…Employees' own race, ethnicity, and age are associated with their perceived job insecurity (Wilson et al. ; Fullerton and Wallace ; Wilson and Mossakowski ; Fullerton and Anderson ). Specifically, Whites are less likely to feel insecure than non‐Whites, and older/mid‐career employees are more likely to feel vulnerable (Newman ; Fullerton and Wallace ; Mendenhall et al.…”
Section: The Role Of Managersmentioning
confidence: 99%
“…; Wilson and Mossakowski ). For example, one study using 2000 to 2010 waves of the General Social Survey finds that the odds of high perceived job insecurity are 53 percent greater for African Americans and 77 percent greater for Hispanics, as compared with Whites (Fullerton and Anderson ). Those with less education also report higher perceived job insecurity (Elman and O'Rand ).…”
Section: The Role Of Managersmentioning
confidence: 99%